Defected Photonic Crystal Array Using Porous GaN as Malaria Sensor. Issue 1 (July 2021) - Tammam, M.T.; Zaky, Zaky A.; Sharma, Arvind; Matar, Z.S.; Aly, Arafa H.; Mohaseb, M.A.
Abstract: A defective one-dimensional photonic crystal is investigated as a biosensor to detect malaria disease. The proposed photonic structure is air/(GaN/Porous GaN) N /Sample/(GaN/Porous GaN) N /Substrate. The red blood cells sample of the human being is used as a sample defect in the proposed optical device. The pioneer transfer matrix method is used to analyze the transmittance spectra. A change in sample refractive index highly affects the transmittance resonant peak and this shift in the peak plays a key role in the operation of the device. The relatively high figure of merit of 1022 RIU −1 with a sensitivity of 1472 nm/RIU and quality factor of 1076 is detected. The proposed sensor is relatively better than others available to detect malaria disease.